Perlindungan Anak Angkat dalam Undang-Undang Nomor 23 Tahun 2002 dalam Perspektif Hifdz Al-Nasl Al-Ghazali - Nasruddin, Nasruddin; Wasman, Wasman; Rofii, Ahmad; Setyawan, Edy; Fansuri, Hamzah (El 'Ailaah, 2025)
This study aims to analyze and explore legal protection for adopted children in the perspective of Law Number 23 of 2002 concerning Child Protection, by linking it to the hifdz al-nasl thinking according to Imam Al-Ghazali. Adoption in Indonesia is regulated by law to ensure the protection of the rights of adopted children, including the right to education, health, and inheritance. However, there are still various challenges in the implementation of adoption, such as the lack of public understanding of legitimate procedures and the existence of illegal adoption. In the context of Islamic family law, Imam Al-Ghazali's thinking on the protection of adopted children emphasizes the importance of maintaining the honor and welfare of children, although it does not change the status of their descendants. Protection of adopted children according to Al-Ghazali includes physical, social, and emotional aspects, and prioritizes the principle of hifdz al-nasl or protection of descendants. This study suggests the need for increased legal counseling and wider access to justice to improve the practice of adoption in Indonesia, as well as optimizing protection for adopted children so that they can grow up with their rights guaranteed. This study integrates the positive law approach and Islamic thought to provide a comprehensive picture of the protection of adopted children in Indonesia.